The Combination of DAT-SPECT, Structural and Diffusion MRI Predicts Clinical Progression in Parkinson’s Disease - Lorio, Sara; Sambataro, Fabio; Bertolino, Alessandro; Draganski, Bogdan; Dukart, Juergen (Frontiers in Aging Neuroscience, 2019)
There is an increasing interest in identifying non-invasive biomarkers of disease severity and prognosis in idiopathic Parkinson's disease (PD). Dopamine-transporter SPECT (DAT-SPECT), diffusion tensor imaging (DTI) and structural magnetic resonance imaging (sMRI) provide unique information about the brain’s neurotransmitter and microstructural properties. In this study, we evaluate the relative and combined capability of these imaging modalities to predict symptom severity and clinical progression in de novo PD patients. We used MRI, SPECT and clinical data of de novo drug-naïve PD patients (n=205, mean age 61±10) and age-, sex-matched healthy controls (n=105, mean age 58±12). Voxel-based group comparisons and covariance analyses were applied to characterize baseline disease-related alterations for DAT-SPECT, DTI and sMRI. Cortical and subcortical alterations in de novo PD patients were found in all evaluated imaging modalities, in line with previously reported midbrain-striato-cortical network alterations. The combination of these imaging alterations was reliably linked to clinical severity and disease progression in this patient population. Therefore the combination of DAT-SPECT with MRI provides a biomarker of disease severity and prognosis that can be integrated into clinical trials of PD therapy.